Development of a contact-less cryogenic rotation mechanism employed for a polarization modulator unit in cosmic microwave background polarization experiments. (September 2019) - Sakurai, Yuki; Matsumura, Tomotake; Katayama, Nobuhiko; Iida, Teruhito; Komatsu, Kunimoto; Sugai, Hajime; Ohsaki, Hiroyuki; Terao, Yutaka; Hirota, Yukimasa; Enokida, Hisashi
Abstract: We present the design and the performance of a contact-less cryogenic rotation mechanism used in cosmic microwave background (CMB) experiments. A precise measurement of the CMB polarization is possible to verify the cosmic inflation theory that describes the very beginning (10 −38 seconds) of the early universe. The polarization modulator, that rotates a half wave plate continuously at the aperture of the telescope, is one of the key instruments in the experiments. In order to reduce noise and systematic uncertainties, the polarization modulator is required a stable rotation with minimal heat dissipation in a cryogenic environment less than 20 K. Thus, we adopted the rotation mechanism that combines completely contact-less bearing and motor, a superconducting magnetic bearing, and a hollow bore synchronous motor. The heat dissipation and the load torque due to the friction can be minimized by avoiding physical contacts. We constructed the prototype of the rotation mechanism and carried out mechanical and thermal performance tests. A continuous rotation test in cryogenic temperature is performed, and it is confirmed that the rotation stability is less than 1% with the rotation frequency between 0.5 Hz and 3.0 Hz. We also conducted a thermal performance test, and obtained the heat dissipation at the rotor of 9.0 mW. We discussed the reduction of heat dissipation using a developed magnetic circuit with improved magnetic field uniformity.